The Stoics on the Good, the Evil and the Indifferents - Protopapas-Marneli, Maria (Peitho. Examina Antiqua, 2025)
In this paper, we examine the concept of evil in Early Stoicism, which is assessed alongside the concepts of good and indifferents within the Stoic classification of things that partake in essence. Adopting the Socratic theory of virtue, which holds that virtue can be taught, the Stoics divided humanity into two categories: the wise (those who act according to reason and are virtuous) and the fools (those who lack reason and are, therefore, ignorant and bad). In this framework, they introduced the notion of the ‘human in progress,’ a state attainable by all who make continuous and diligent effort. If this model holds true, why then do evil people exist, and why does evil persist in the world? The Stoics, we believe, ultimately provide a solution to this problem, which we aim to explore and substantiate in this paper.